2011
DOI: 10.1111/j.1439-0310.2011.01988.x
|View full text |Cite
|
Sign up to set email alerts
|

Duet Function in the Yellow‐Naped Amazon, Amazona auropalliata: Evidence From Playbacks of Duets and Solos

Abstract: The question of why animals participate in duets is an intriguing one, as many such displays appear to be more costly to produce than individual signals. Mated pairs of yellow-naped amazons, Amazona auropalliata, give duets on their nesting territories. We investigated the function of those duets with a playback experiment. We tested two hypotheses for the function of those duets: the joint territory defense hypothesis and the mate-guarding hypothesis, by presenting territorial pairs with three types of playba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 40 publications
(110 reference statements)
0
25
0
Order By: Relevance
“…The traditional manner in which the conflict vs. cooperation dichotomy has been addressed should also be re‐examined in the light of our results. The traditional experimental design contrasts the sex‐specific responses of a mated pair to duet and single‐sex playbacks, with the prediction that pairs will either respond more strongly to duets or equally strongly to all playbacks if they serve a cooperative, resource defence function, while responses to same‐sex playback will be higher if duets serve a mate‐guarding function (Levin ; Hall & Magrath ; Hall & Peters ; Benedict ; Douglas & Mennill ; Dahlin & Wright ). In some cases, support for a mate‐guarding hypothesis has stemmed from strong intrasexual responses by females to solo vocalizations, while males respond equally to solos and duets (Rogers et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional manner in which the conflict vs. cooperation dichotomy has been addressed should also be re‐examined in the light of our results. The traditional experimental design contrasts the sex‐specific responses of a mated pair to duet and single‐sex playbacks, with the prediction that pairs will either respond more strongly to duets or equally strongly to all playbacks if they serve a cooperative, resource defence function, while responses to same‐sex playback will be higher if duets serve a mate‐guarding function (Levin ; Hall & Magrath ; Hall & Peters ; Benedict ; Douglas & Mennill ; Dahlin & Wright ). In some cases, support for a mate‐guarding hypothesis has stemmed from strong intrasexual responses by females to solo vocalizations, while males respond equally to solos and duets (Rogers et al.…”
Section: Resultsmentioning
confidence: 99%
“…These vocalizations appear to be a more complex behaviour than signalling alone, as they involve spatial and temporal coordination, increased attentiveness and potentially additional practice (Hall ). The complex nature of duet signals raises intriguing questions about how duets differ in form and function from solo vocalizations (Hall , ; McGregor ; Dahlin & Wright ). For this reason, duets have become an area of intense interest in the last couple of decades, with more than 60 new avian publications since 1990 alone (of more than 90 in the field overall).…”
Section: Introductionmentioning
confidence: 99%
“…A high degree of convergence and coordination between the sexes in playback responses has been found for a few other species (Benedict, ; Dahlin & Wright, ; Hall & Peters, ; Quirós‐Guerrero et al, ). In yellow‐naped amazons ( Amazona auropalliata ), partners did not differ in the approach behavior or vocal output (Dahlin & Wright, ). Similarly, in purple‐crowned fairy‐wrens ( Malurus coronatus ), partners coordinate their approach to the speaker and their vocal output in response to playbacks of duets (Hall & Peters, ).…”
Section: Discussionmentioning
confidence: 99%
“…Rufous horneros normally respond to conspecific playbacks by approaching and perching high on the speaker substrate (tree or light pole) instead of approaching the speaker itself or branches close to it, which is a typical response for many birds (Dahlin & Wright, ; Funghi, Cardoso, & Mota, ; Hall, ; Rogers et al, ). Rufous horneros then usually sing once and do not sing again for an average of 5.63 ± 3.81 min (mean ± SD , n = 110) after the playback.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the majority of the species of parrots examined in both our literature search and our survey of Amazona do not defend resource-based territories and are not considered territorial in the same sense that the typical songbird is, although mated pairs in many species of parrots will vigorously defend the area directly around their nest cavity (Toft and Wright 2015). For example, the Yellow-naped Amazon produces pair duets around its nest site that appear to function in nest defence (Dahlin and Wright 2012a; Dahlin and Wright 2012b); these duets exhibit vocal dialects that are congruent with those seen in contact calls (Wright and Dorin 2001). Finally, both reviews of songbird dialects found an association of vocal dialects with migratory status, such that sedentary species and those with longer breeding seasons were more likely to have dialects, although dialects were also widespread in migratory species (Handley and Nelson 2005; Podos and Warren 2007).…”
Section: Comparisons With Songbirdsmentioning
confidence: 99%